Physical and training characteristics of top-class marathon runners - Billat. V. L.; Demarle, A.; Slawinski, J.; Paiva, M.; Koralsztein, J. P. (Medicine & Science in Sports & Exercise, 2001)
Purpose: This study compares the physical and training characteristics of top-class marathon runners (TC), i.e., runners having a personal best of less than 2 h 11 min for males and 2 h 32 min for females, respectively, versus high-level (HL) (< 2 h 16 min and < 2 h 38 min). Methods: Twenty marathon runners (five TC and HL in each gender) ran 10 km at their best marathon performance velocity (vMarathon) on a level road. This velocity was the target velocity for the Olympic trials they performed 8 wk later. After a rest of 6 min, they ran an all-out 1000-m run to determine the peak oxygen consumption on flat road (&OV03122peak). Results: Marathon performance time (MPT) was inversely correlated with &OV03122peak (r = -0.73, P < 0.01) and predicted 59% of the variance of MPT. Moreover, TC male marathon runners were less economical because their energy cost of running (Cr) at marathon velocity was significantly higher than that of their counterparts (212 +/- 17 vs 195 +/- 14 mL.km-1.kg-1, P = 0.03). For females, no difference was observed for the energetic characteristics between TC and HL marathon runners. However, the velocity reached during the 1000-m run performed after the 10-km run at vMarathon was highly correlated with MPT (r = -0.85, P < 0.001). Concerning training differences, independent of the gender, TC marathon runners trained for more total kilometers per week and at a higher velocity (velocity over 3000 m and 10,000 m). Conclusion: The high energy output seems to be the discriminating factor for top-class male marathon runners who trained at higher relative intensities. Med Sci Sports Exerc 2001 Dec;33(12):2089-2097